Slide25.JPG

Slide26.JPG

Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class


Transcript

Ex 3.3, 10 Prove that sin⁑(𝑛 + 1)π‘₯ sin⁑(𝑛 + 2)π‘₯+cos⁑(𝑛 + 1)π‘₯ cos⁑(𝑛 + 2)π‘₯=cos⁑π‘₯ Solving L.H.S. We know that cos ( A – B) = cos A cos B + sin A sin B Here, A = (n + 1)x ,B = (n + 2)x Hence sin⁑(𝑛+1)π‘₯ sin⁑(𝑛+2)π‘₯+cos⁑(𝑛 + 1)π‘₯ cos⁑(𝑛 + 2)π‘₯ = cos [ (n + 1)x – (n + 2)x ] = cos [ nx + x – nx – 2x ] = cos [ nx – nx + x – 2 x ] = cos (0 – x ) = cos (– x) = cos x = R.H.S. Hence , L.H.S. = R.H.S. Hence proved

Ask a doubt
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 13 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.